Identifying Errors made by EFL College Students in Dictation (Journal of the College of Basic Education, 2023)
A test is an important device for teachers and for learners; for teachers inthat it helps to assess the students' EL performance and for learners in that ithelps them to discover the areas of weakness and strength in theirperformances. Dictation is one of the integrative tests that have proved their proficiency inmeasuring different language skills, like listening comprehension and spelling .It is a reading passage (100 to 200 words) which is read by the teacher threetimes at a normal speed . The students' task is to write down what the teacherread in the second reading . However, experienced instructors in the field ofTEFL realise that learners have many errors in writing . Hence, the present study aims at identifying, classification and explainingthe errors that EFL college students make during applying dictation tests . The sample of the study is 55 students randomly chosen from the second-year students at the Department of English, College of Basic Education ,Al-Mustansiriyah University during the academic year 2005 / 2006. The instrument of the study is a ready test which consists of a 162- wordpassage. The passage is intended to test advanced students' dictation. The test issubmitted to a jury of specialists to ensure its validity. The test results revealed that the sample subjects have many errors whichthe researcher classified into comprehension, grammatical and spelling errors.Spelling errors formed the largest percentage of the total number of errorswhich are, in turn, classified into subcategories . In the light of the obtained results some conclusions are drawn, number ofrecommendations are made, and several suggestions for further research arepresented .